Seismic response of a base isolated cable-stayed bridge under near-fault ground motion excitations / Ahad Javanmardi … [et al.]. - Javanmardi, Ahad; Ibrahim, Zainab; Gheadi, Khaled; Gordan, Meisam; Jameel, Mohammed; Hanif, Usman (Institute of Research Management and Innovation and UiTM Press, 2018)
Nowadays, development of cable-stayed bridges is increasing around the world. The mitigation of seismic forces to these bridges are obligatory to prevent damages or failure of its structural members. Herein, this paper aimed to determine the near-fault ground motion effect on an existing cablestayed bridge equipped with lead-rubber bearing. In this context, Shipshaw cable-stayed bridge is selected as the case study. The selected bridge has a span of 183.2 m composite deck and 43 m height of steel tower. 2D finite element models of the non-isolated and base isolated bridges are modelled by using SAP2000. Three different near-fault ground motions which are Tabas 1978, Cape Mendocino 1992 and Kobe 1995 were subjected to the 2D FEM models in order to determine the seismic behaviour of the bridge. The near-fault ground motions were applied to the bridge in the longitudinal direction. Nonlinear dynamic analysis was performed to determine the dynamic responses of the bridge. Comparison of dynamic response of nonisolated and base isolated bridge under three different near-fault ground motions were conducted. The results obtained from numerical analyses of the bridge showed that the isolation system lengthened the period of bridge and minimised deck isplacement, base shear and base moment of the bridge. It is concluded that the isolation system significantly reduced the destructive effects of near-fault ground motions on the bridge.